The applicability of ICMS-e in Paraná State municipalities - Aguirre, Joelma Leopoldino; Nogueira, Vilma Aparecida de Moraes; Stefanello, Paulinho Rene; Fernandes, Alexandre Machado; Silva, Frederico Fonseca da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The ICMS-e is an important instrument of public politics focused to environment, compensating financially cities of Parana state (Brazil) that have in their territory Environmental Preservation Areas and / or Water Source Public Supply. The general purpose of this study was verifying the applicability of resources in the municipalities benefit from income derived from the ICMS in the State of Paraná. The methodology is based on bibliographic and documentary review and interviews with state and local public officials, fiscal and environmental areas. It was found through research low percentage of application of ICMS-e on actions focused at environmental preservation, even in municipalities highly dependent of this source of revenue for your maintenance. It is suggested environmental education and awareness of the municipal government with the inclusion in the Budget Guidelines Law (LDO) and Annual Budget Law (LOA) of significant and sufficient part of the resources generated by the environment programs and effective actions for the preservation and environmental maintenance.